Sirt3 Regulates Response to Oxidative Stress by Interacting with BER Proteins in Colorectal Cancer - J. Kabzinski; A. Walczak; I. Majsterek (Genetics Research)
The oxidative damages are well-recognized factors in the pathogenesis of colorectal cancer (CRC). Increased levels of reactive oxygen species (ROS) can lead to oxidative DNA damage, which, if unrepaired, can be an underlying cause of cancerogenic transformation. To defend against these threats, cells have developed a range of defense mechanisms. One of the most important protection mechanisms is DNA repair systems, both nuclear and mitochondrial. Sirt3 is a mitochondrial protein involved in regulating NEIL1, NEIL2, MUTYH, APE1, and LIG3 proteins, which are involved in DNA repair, including mitochondrial repair through mtBER (mitochondrial Base Excision Repair). In this work, we show that NEIL1, NEIL2, MUTYH, APE1, and LIG3 are regulated by Sirt3 through deacetylation, and moreover, Sirt3 is directly involved in physical interaction with MUTYH, NEIL1, and APE1, which indicates the controlling role of Sirt3 over the mtBER mechanism. Also, if the cells deprived of Sirt3 are exposed to oxidative stress, altered levels of those proteins can be observed, which supports the theory of the regulatory role of Sirt3. Finally, to fully confirm the role of Sirt3 in DNA repair, we examined its role in apoptosis and found the impact of this protein on cell survival rate. Using the knowledge obtained in the course of conducted experiments, we postulate consideration of Sirt3 as a target in the rising vulnerability of cancer cells during therapy and therefore increasing the effectiveness of cancer treatment.